Verbal complement clauses : a minimalist study of direct perception constructions - Felser, Claudia (Linguistik aktuell ;, 1999)
This monograph examines the syntax of bare infinitival and participial complements of perception verbs in English and other European languages, and investigates the general conditions under which verbal complement clauses are licensed. The introductory chapter is followed by an overview of the major syntactic and semantic characteristics of non-finite complements of perception verbs in English. The third chapter presents an analysis within the framework of Chomsky's (1995) Minimalist Program according to which event-denoting complements are minimally realised as projections of an aspectual hea.